PEMAHAMAN ANTICIPATORY GUIDANCE DENGAN PERTUMBUHAN BALITA - Siti Indatul Laili (Universitas Pesantren Tinggi Darul Ulum, 2023)
Toddlerhood is an important period in the growth process and is a determinant of the success of children's growth which can be influenced by parents' understanding of anticipatory guidance. The purpose of this study was to determine the understanding of anticipatory guidance on toddler growth at Posyandu Balongmojo Puri, Mojokerto Regency. The research design was cross-sectional, the population in this study were all mothers and toddlers at Posyandu Balongmojo Puri, Mojokerto Regency, totaling 63 respondents. The sample for this study were all mothers and toddlers in Posyandu Balongmojo, Puri, Mojokerto Regency, totaling 63 respondents who were taken by total sampling technique. The research instrument was a questionnaire with 100% valid and reliable test results with ? = 0.891 and scales. This research was conducted at the Balongmojo Posyandu, Puri, Mojokerto Regency in August 2021. Data processing was carried out by editing, coding, scoring, and data analysis using Microsoft Excel cross tables. The results showed that almost all of the mothers had a good understanding of having toddlers with good growth as many as 48 respondents (76.2%). A mother's good understanding of anticipatory guidance can care for children well and be able to meet the child's needs according to age so that the child reaches a normal growth and development phase. Keywords: Anticipatory Guidance, Growth, Toddlers